A Developed Optimization Model for Mass Production Scheduling Considering the Role of Waste Materials - Chetthamrongchai, Paitoon; Stepanenko, Olga Gennadevna; Saenko, Natalya Ryafikovna; Bakhvalov, Sergey Yurevich; Aglyamova, Gulnaz; Iswanto, A. Heri (International Journal of Industrial Engineering and Management, 2022)
Planning, scheduling and delivery of shipments in workshops and factories active in the field of custom manufacturing industries are two important arms in the decision-making process that are used to optimize or reduce the adverse effects of problems in production, so this is one of the important pillars within any company or manufacturing plant. The importance of this issue will become clear when this tool is used in the real world and the production platform to benefit the companies. In this research, we will investigate a medium-term period and a short-term schedule for the production of carton sheets in the printing and packaging industry, and provide a method for separating cutting and scheduling models, as well as an innovative method for the scheduling. The result of the research is the comparison of the proposed method with the common method used in the factory to measure the efficiency. Article history: Received (January 1, 2022); Revised (May 18, 2022); Accepted (May 19, 2022); Published online (June 8, 2022)